2022
DOI: 10.1177/09636625221092696
|View full text |Cite
|
Sign up to set email alerts
|

Engagement patterns with female and male scientists on Facebook

Abstract: Social networks are becoming powerful agents mediating between science and the public. Considering the public tendency to associate science with men makes investigating representations of female scientists in social media important. Here we set out to find whether the commenting patterns to text-based science communication are similar. To examine these, we collected and analyzed posts (165) and their comments (10,006) published between 2016 and 2018 on an Israeli popular science Facebook page. We examined post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…James Randerson, the Guardian's environment and science news editor, emphasized that reporters should view reader interactivity "as part of the journalistic process, not as a kind of add-on" [Fahy & Nisbet, 2011, p. 785]. While we recognize that online news comments sections can be problematic sites for attracting abuse and harassment -particularly when research is controversial [Anderson, Brossard, Scheufele, Xenos & Ladwig, 2013] or when writers are women [Dalyot, Rozenblum & Baram-Tsabari, 2022] or from marginalized community groups [Saldaña & Proust, 2022], we encourage SNWs, serving as science communicators, to embrace scholarly recommendations and acknowledge their professional commitment to engage actively in dialogue with the public. They possess technical expertise and staff capable of engaging in meaningful discussions with readers interested in science, including individuals who can engage in constructive arguments drawing upon their knowledge and experiences and those who simply seek answers and clarification.…”
Section: Discussionmentioning
confidence: 99%
“…James Randerson, the Guardian's environment and science news editor, emphasized that reporters should view reader interactivity "as part of the journalistic process, not as a kind of add-on" [Fahy & Nisbet, 2011, p. 785]. While we recognize that online news comments sections can be problematic sites for attracting abuse and harassment -particularly when research is controversial [Anderson, Brossard, Scheufele, Xenos & Ladwig, 2013] or when writers are women [Dalyot, Rozenblum & Baram-Tsabari, 2022] or from marginalized community groups [Saldaña & Proust, 2022], we encourage SNWs, serving as science communicators, to embrace scholarly recommendations and acknowledge their professional commitment to engage actively in dialogue with the public. They possess technical expertise and staff capable of engaging in meaningful discussions with readers interested in science, including individuals who can engage in constructive arguments drawing upon their knowledge and experiences and those who simply seek answers and clarification.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not necessarily be the case when scientists, such as those in our study, are already well-known or have become more familiar to their audiences through their Facebook pages. Future research should take this into account and examine the role of gender, which has been shown to affect user reactions on social media platforms such as Facebook (Dalyot et al, 2022) and Instagram (Jarreau, Cancellare, et al, 2019). It is still an open question whether gender influences the impact of self-disclosure on perceived competence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while there is agreement that using less complex lan-guage is preferable, there is also the threat that using simplified language can lead to misinterpretations (Rice & Giles, 2017;Wong-Parodi & Strauss, 2014). Prior studies considering the complexity of language on social media platforms have measured complexity manually (Dalyot et al, 2022) or automatically (Hubner & Bond, 2022).…”
Section: Successful Communication On Facebookmentioning
confidence: 99%